PENGARUH TEKNIK PERMAINAN TEBAK GAMBAR UNTUK MENINGKATKAN KEMAMPUAN BERBICARA SISWA DI MTS HASANAH PEKANBARU - Resti, Amelia; ', Erni; ', Mahsyur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study was about the application of guessing games technique in speaking ability of the first year students. The aim of this study was to find out the improvement students’ speaking ability through guessing games technique at MTS Hassanah and to find out the effectiveness of guessing games technique in improving students’ speaking ability. 24 out of 120 students were chosen through cluster random technique sampling. The analysis was based on giving oral test to the students. It was found that there were significant improvement; 4 students (16.7%) were in excellent level, 20 students (83.3%) were in good level, and there is no students in mediocre, poor and very poor level. It implies that the students’ ability falls into good ability level. Based on the result, it is recommended that teachers pay attention more to the students about how to speak English well. It is also important to apply games especially guessing game in the term of motivating the students so that they are brave to speak up and fun to learn English.Key Words: Guessing Games, Technique, Speaking